Proteomic changes in the ileum of sheep infected with Mycobacterium avium subspecies paratuberculosis. (January 2017) - Pisanu, S.; Cubeddu, T.; Uzzau, S.; Rocca, S.; Addis, M.F.
Highlights: Johne's disease (JD) is caused by Mycobacterium avium subsp. paratuberculosis (MAP) and has an economic impact on sheep productions. A shotgun proteomics study was carried out on terminal ileum tissues from infected and uninfected ewes. A large data set of proteomic changes occurring in the infected ileum was generated and analysed. MAP proteins highly expressed in vivo in the infected tissue were identified. The proteins undergoing the most relevant changes are related to host immune response and MAP pathogenesis. Abstract: Johne's disease (JD) is a chronic enteritis of ruminants caused by Mycobacterium avium subspecies paratuberculosis (MAP). To identify the processes activated in the sheep intestine during natural MAP infection, and to provide a panel of differential host and pathogen proteins with diagnostic and prognostic potential, a differential shotgun proteomics workflow, including mass spectrometry, label-free quantisation and pathway analysis, was applied to ileal tissues of ewes with and without JD. Out of 2889 total proteins identified, 384 were differentially expressed and 341 were expressed at a higher level in JD. On the basis of Search Tool for the Retrieval of Interacting Genes/Proteins (STRING) analysis, these proteins were involved in numerous relevant biological networks and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, including inhibition of phagosome acidification (such as V-ATPase), bacterial invasion, leucocyte recruitment and activation, and antimicrobial activity (such as haptoglobin, lactoferrin, cathelicidins, calgranulins and interleukins). A total of 28 MAP proteins were identified, including bacterioferritin, β-lactamase and heparin-binding haemagglutinin (HBHA), a mycobacterial adhesin crucial for dissemination of infection.